341 Is CT Imaging Mandated for Confirming the Diagnosis of Acute Appendicitis in Patients Over the Age of 40?. (19th August 2022) - Shepherd, T; Farah, M; Aljarad, F; Bista, G; El-Gaddal, A; Ng, P
Abstract: Aim: Acute appendicitis remains a largely clinical diagnosis, with clinical scoring systems such as the Alvarado score calculated to give a quantitative assessment of the diagnostic probability. It remains common practice amongst surgeons to rely on CT scanning to confirm the diagnosis however, especially in older patients. Our aim was to assess the diagnostic performance of CT scanning compared with that of the Alvarado score in patients aged over 40 years old. Method: We conducted a retrospective observational study of 149 patients greater than 40 years old who had a diagnosis of acute appendicitis and had undergone an appendicectomy with subsequent histological analysis. Data was extracted from patients' electronic medical records. This was recorded in Microsoft Excel and analysed using NCSS. Results: When using an Alvarado score cut-off point of ≥7, the sensitivity and specificity were 44.1% and 60.0% respectively. The sensitivity of the test improved to 80.3% when using a cut-off point of ≥ 5, however the specificity decreased to 50%. The accuracy improved to 78.1% from 45.3%, when using ≥ 5 as a cut-off point. On the other hand, the sensitivity of the CT scan was 84.9% and the specificity was 45.5%. The accuracy of CT scanning was 81.8%. Conclusions: When comparing performance, pre-operative CT scanning did not show a statistically significant improvement in the diagnosis of acute appendicitis relative to Alvarado score. We recommend using an Alvarado score cut-off point of ≥ 5 to aid in diagnosing appendicitis in patients older than 40, as it accounts for a higher sensitivity.